The Use of Force and Self-determination: Parsing Indeterminacy - Forcese, Craig (Polish Review of International and European Law, 2025)
Hersch Lauterpacht observed in 1952 that “if international law is, in some ways, at the vanishing point of law, the law of war is, perhaps even more conspicuously, at the vanishing point of international law.”[1] More than 70 years later, Lauterpatch’s observation overstates the indefiniteness of modern international humanitarian law – the jus in bello or law of armed conflict governing the means and methods of armed conflict. However, it remains a fair critique of the jus ad bellum – the law that addresses the “rightness” of a recourse to force. Even more pointed would be a codicil, addressing the relationship between this jus ad bellum and the right of self-determination: The vanishing point at the vanishing point of international law is the relationship between the regulation of force and the right to self-determination. At this convergence point, two challenging questions of high politics intertwine to compound the indeterminacy of the law. The result is an area fertilized with opinions but hobbled with uncertainty. This fact is not accidental. States have little incentive to lay a roadmap for their lawful forcible dismemberment. Still, it may be possible to tease from the accrual of state practice answers to some questions in this area if factual scenarios are carefully parsed.